Pengaplikasian Smartphone sebagai Media Komunikasi Interpersonal Dikalangan Pegawai di Kementerian Agama Kabupaten Aceh Barat - Al-Imam (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2021)
The use of smartphones is now not a strange thing among office employees. This study wants to see how the application of smartphones as a medium of interpersonal communication among employees of the Ministry of Religion in West Aceh District because as is well known, the function of smartphones is not just to call each other. The features of the smartphone allow people to communicate in various ways, besides that it allows people to use it for a specific purpose, in addition to communicating. By using a qualitative method approach, the researchers found that it turns out that employees of the Ministry of Religion in West Aceh District have applied smartphones with various features they have as media to communicate intensively with other employees around the office without the need to do it face-to-face. Smartphones have become a much-needed communication media for employees of the ministry of religion in West Aceh District, although there are adverse impacts on employees when using smartphones, such as reducing discipline and reducing productivity at work. To overcome the negative use, it requires rules and supervision from the office leadership.